Brain Cavernomas Induced By Radiotherapy in the Patient With Acute Lymphocytic Leukemia (ALL) - Saeidi Saedi, Hamid; Alijani, Babak; Emam Hadi, Mohammadreza; Shahrokh, Shahrokh; Behzadnia, Hamid; Kiumarcy, Adel (Reports of Radiotherapy and Oncology, 2015)
Introduction: Radiotherapy is considered the main part of the curative and preventive regimes in the pediatric cancer especially has been highly used in acute lymphocytic leukemia (ALL) as prophylaxis. A large number of the radiotherapy secondary delayed effects have been well known. Case Presentation: In present study, we has introduced a 15-year-old boy with ALL underwent chemotherapy and radiotherapy. Who had generalized tonic-colonic seizure which has been lasted 10 minutes (without any previous history). The patient with ALL ten years ago has been treated by chemotherapy and whole brain prophylactic radiotherapy with dose 1200 cGy/120 cGy/10. In his MRI a heterogeneous mass with the dimensions 3 × 2 cm in the left frontal lobe with the peripheral edema and after complete the diagnose process the final report of this mass was Cavernoma. Conclusions: There has been identified a clear link between radiotherapy and brain cavernoma; therefore, it should be considered in differential diagnosis of brain hemorrhagic lesions in each patient with the history of radiotherapy of the central nervous system. This risk is higher when the patient has the history of the brain radiotherapy in childhood.